Carrier-phase Ambiguity Success Rates for Integrated GPS-Galileo Satellite Navigation - Verhagen, S.; Teunissen, Peter; Odijk, Dennis (Institute of Electronics, Information and Communication Engineers (IEICE), 2007)
High-precision Global Navigation Satellite System (GNSS) positioning results are obtained with carrier phase measurements, once the integer cycle ambiguities have been successfully resolved. During the last decade much experience has been gained on fast and precise positioning with GPS as a dual-frequency system. The modernization of the GPS and the advent of Galileo will together lead to a truly multi-frequency civil GNSS, enhancing the capability of resolving the carrier phase ambiguities. In this paper the ambiguity success rates will be presented for different measurement scenarios and differentGNSSs (e.g. modernized GPS, Galileo, integrated GPS-Galileo), emphasizing the role played by multiple frequencies and the number of satellites tracked.